The effect of teaching socio-scientific issues with cooperative learning model on pre-service teachers’ argumentation qualities - Atabey, Nejla; Arslan, Ayten (My University, 2020)
In this study, the effect of teaching socio-scientific issues with cooperative learning model on the argumentation qualities of pre-service teachers was investigated. The study group consisted of 40 primary school pre-service teachers studying at Muş Alparslan University. Exploratory sequential research design was used in this study. In the quantitative dimension of the study, quasi-experimental design with pre-test-post-test control group was carried out. In this context, a control and 2 experimental groups were formed. Jigsaw and learning together methods were implemented with the experimental groups and activities suitable for group works were carried out with the control group. In the qualitative dimension, semi-structured interviews were conducted with the pre-service teachers. At the end of the study, the argumentation qualities of the pre-service teachers were evaluated with descriptive analysis and semi-structured interviews were evaluated with content analysis. Findings revealed that cooperative learning methods, especially jigsaw method, positively affect the pre-service teachers' arguments,
Keywords: Eğitim, Eğitim Araştırmaları; Argumentation qualities; Cooperative learning; Primary school pre-service teachers; Socio-scientific issues